Langmuir-Schaefer Perylene Derivative Films: Influence of the Molecular Chemical Structure on the Supramolecular Arrangement - Fernandes, José Diego [UNESP]; Pazin, Wallance Moreira [UNESP]; Macedo, Wagner Costa [UNESP]; Ruiz, Gilia Cristine Marques [UNESP]; Constantino, Carlos José Leopoldo [UNESP] (American Chemical Society (ACS), 2021)
Since the optical and electrical properties of organic thin films devices depend on their supramolecular arrangement and the molecular chemical structure, the understanding of such characteristics is essential for the optimization of these devices. In this study, we determine the supramolecular arrangement of thin films produced using the Langmuir-Schaefer (LS) technique and explain how its supramolecular arrangement is affected by the molecular chemical structure using two perylene derivatives: bis-butylimide (BuPTCD) and bis-phenethylimide (PhPTCD). The optical absorption measurements reveal that both films grow homogeneously and indicate that the presence of H aggregates (forbidden emission) is higher for BuPTCD LS film than for PhPTCD LS film. Atomic force microscopic analysis shows that the PhPTCD LS film is rougher than the BuPTCD film. In addition, FTIR analyses indicate that both films have head-on molecular organization. XRD patterns reveal that both the BuPTCD LS film and the PhPTCD LS film are crystalline, but that crystallinity is more prevalent in the BuPTCD LS film. Thus, the results show that the difference presented in the chemical structures leads the films to have different supramolecular arrangements, with consequences for their optical properties.